Drug utilization study in the otorhinolaryngology department in a tertiary care hospital - Sridevi, S. A.; Janagan, T.; Rathnasamy, P.; Rajarajeswari, R. (International Journal of Basic & Clinical Pharmacology, 2017)
Background: Drug utilization is defined by the World Health Organization (WHO) as the marketing, distribution, prescription, and use of drugs in society, with special emphasis on the resulting medical, social, and economic consequences. The aim of this study was to evaluate the pattern of prescription and then drug utilization in outpatient (OPD) of the Department of Otolaryngology in a tertiary care teaching hospital. Methods: This was a retrospective study conducted at the A.C.S. medical college and hospital, Chennai for a period of 7 months. All the patients who attended the Ear Nose and Throat (ENT) OPD were included. The total number who attended the OPD was 10,249 which include 6,956 new cases and 3313 old cases. Results: The antibacterials commonly used were β Lactams (56%), macrolides (14%), fluoroquinolones (12%), aminoglycosides (8%). Among the penicillin group, the commonest drug prescribed was a combination of amoxicillin and clavulanic acid (27%), in cephalosporins was cefixime + clavulanic acid (19%). Aminoglycosides include gentamycin in refractory cases. Fluoroquinolones include ciprofloxacin and levofloxacin. Others Drugs like antihistamines and mucolytics were prescribed in 27%, anti- ulcer drugs in 36% cases, analgesics in 33% cases and herbal medicines in 4%. The average number of drugs used in each prescription was 3.20. All the drugs were prescribed with brand names. The average cost per prescription per day for OPD patients is 37 Rupees. Conclusions: β Lactams were commonly used antibacterials in the otorhinolaryngology department.